NIVEL DE SATISFACCIÓN DE LOS USUARIOS DEL CENTRO DE SALUD DE LA PARROQUIA ISLA DE BEJUCAL DEL CANTÓN BABA - Cercado Alava, Maria Jose (2019)
Health care is still being debated as a social right that every citizen of the country has, however, there are no certain criteria on what kind of benefit the right to health must include, all these debates arise as a result of what is important and neuralgic that is the care of physical integration in each person, this is the analysis of the contribution that the public sector must provide in guaranteeing access to this right in an integral manner and characterized by timely, warm and efficient attention. The present investigation is oriented to analyze institutional weaknesses that the health center of the Parish of Isla de Bejucal of the Baba canton possesses, which cause not achieving an adequate level of satisfaction in the users of said locality and its surrounding sectors, it is necessary to mention that when there are problems within an institution whose competence is to take care of and prevent adverse situations in the patients' health, it is a sign that the offer of a social service, such as medical care, is not fully met.